Pay-What-You-Want Pricing Schemes: A Self-Image Perspective - Goytom Abraha Kahsay; Margaret Samahita (University of Copenhagen, Department of Food and Resource Economics (IFRO), 2014)
Pay-What-You-Want (PWYW) pricing schemes are becoming increasingly popular in a wide range of industries. We develop a model incorporating self-image into the buyer's utility function and introduce heterogeneity in consumption utility and image-sensitivity, which generates different purchase decisions and optimal prices across individuals. When a good is sold at a fixed price higher than a threshold value, a price that the individual thinks is fair, the adoption of PWYW increases his utility and hence results in a weakly higher purchase rate. When a good is sold at a fixed price lower than this threshold, however, PWYW can lead to a lower utility. This may result in a lower purchase rate and higher average price, in line with previously unexplained evidence from field experiments. Moreover, an increase in the threshold value decreases the buyer's utility and may further lower the purchase rate, possibly resulting in a further increase in purchase price. Using simple assumptions of quadratic self-image function and uniformly distributed individual preferences, we investigate the conditions under which PWYW yields higher total welfare.
Keywords: D03; D11; D49; D64; D82; 330; Pay-what-you-want; self-image; fairness; voluntary contribution